Pengaruh Penyakit Komorbid Diabetes Melitus Terhadap Pasien Covid 19 Di Rumah Sakit YARSI - Muhammad Gilang Kartiko; Intan Kumala Dewi; Muhammad Arsyad (Junior Medical Journal, 2023)
Coronavirus Disease (COVID-19) is a disease caused by the SARS-CoV-2 virus, the SARS-CoV-2 virus has a positive single-stranded RNA genome. Generally, patients infected with the SARS-CoV-2 virus have a fever, dry cough, shortness of breath, headache and sore throat symptoms. A report in China showed that patients with diabetes had a 32.4% higher cardiovascular disease prevalence than those without diabetes. One of the causes of a person who has diabetes is a genetic history from parents—the habit of consuming bad things that parents do results in their offspring getting diabetes. This study was conducted to determine the effect of comorbid diabetes mellitus on the severity of COVID-19 patients. This research is quantitative with a case-control approach. This type of research is an analytic observational study. The population and samples in this study were all medical record data of patients infected with COVID-19 at YARSI Hospital. Data collection techniques using secondary data in the form of medical records of COVID-19 patients at YARSI Hospital. The data measurement technique uses the bivariate analysis method. Then the data were processed using SPSS. The results showed that there were 795 patients affected by COVID-19 at YARSI hospital, with 178 patients (22.38%) having comorbid diabetes mellitus, 20 patients (11.23%) having comorbid diabetes mellitus without confounding factors and 12 patients (60%) having comorbid diabetes mellitus without confounding factors and data completeness. This study showed no effect of comorbid diabetes mellitus on COVID-19, with a p-value of 0.338.